2019
DOI: 10.1098/rsos.190908
|View full text |Cite
|
Sign up to set email alerts
|

Will natural resistance result in populations of ash trees remaining in British woodlands after a century of ash dieback disease?

Abstract: Novel pests and diseases are becoming increasingly common, and often cause additional mortality to host species in the newly contacted communities. This can alter the structure of the community up to, and including, the extinction of host species. In the last 20 years, ash dieback (ADB) disease has spread into Europe from East Asia. It has caused substantial mortality in ash tree ( Fraxinus excelsior L . ) populations. However, a proportion of the individuals in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…In the past decades, pedunculate oak forests in Europe have been subjected to numerous stress factors, such as low underground water level [7], drought stress [8], pest and diseases [9,10], and climate change [11]. As a consequence of their negative impact, trees' health status and growth rate have frequently deteriorated, sometimes resulting even in premature death [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decades, pedunculate oak forests in Europe have been subjected to numerous stress factors, such as low underground water level [7], drought stress [8], pest and diseases [9,10], and climate change [11]. As a consequence of their negative impact, trees' health status and growth rate have frequently deteriorated, sometimes resulting even in premature death [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…Although a minor proportion of ash trees is likely inheriting resistance against ADB (Plumb et al 2019; Kjær et al, 2012), this alone will not guarantee that the ash population will recover after the disease has reached an equilibrium state. Evans (2019) simulated that long-term recovery of ash is highly dependent on the proportion of ash trees carrying natural resistance and secondly on the degree of heritability of resistance. However, even under extreme high heritability assumptions, long-term recovery under natural conditions will remain low when the founder population consists of only few trees.…”
Section: Discussionmentioning
confidence: 99%
“…This verifies that disease resistance is partially under genetic control. Assuming that the heritability of resistance is 0.5 and the frequency of resistant trees in pre-diseased ash forests is about 10%, model simulations estimated that ash populations in the UK woodlands would still exist in 100 years but decrease to about one-third of current levels (Evans 2019). It has thus been suggested that genetic variation in resistance may prove to be a long-term solution to ash dieback if natural selection is coupled with artificial selection (McKinney et al 2014;Evans 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the heritability of resistance is 0.5 and the frequency of resistant trees in pre-diseased ash forests is about 10%, model simulations estimated that ash populations in the UK woodlands would still exist in 100 years but decrease to about one-third of current levels (Evans 2019). It has thus been suggested that genetic variation in resistance may prove to be a long-term solution to ash dieback if natural selection is coupled with artificial selection (McKinney et al 2014;Evans 2019). However, the frequency of ash trees with reasonable to high levels of genetic resistance (defined as crown damage below 10%) within natural populations is low, 1-5% (Kjӕr et al 2012;McKinney et al 2014), and due to their long lifetime, no studies have yet measured the realised lifetime fitness of healthy trees with respect to their more susceptible neighbours in the surroundings (Kjaer et al 2012).…”
Section: Introductionmentioning
confidence: 99%